Salsolinol Up‐Regulates Oxytocin Expression and Release During Lactation in Sheep. (3rd March 2016) - Górski, K.; Marciniak, E.; Zielińska‐Górska, M.; Misztal, T.
Abstract : Salsolinol (1‐methyl‐6, 7‐dihydroxy‐1, 2, 3, 4‐tetrahydroisoquinoline) is a dopamine‐derived compound present in the central nervous system and pituitary gland. Several previous studies on lactating sheep and rats have reported that salsolinol plays a crucial role in the regulation of prolactin secretion. The present study investigated the effects of salsolinol, which was infused into the third ventricle of the brain, on oxytocin expression and release in lactating sheep, 48 h after weaning of 8‐week‐old lambs. Serial 30‐min infusions of salsolinol and vehicle were performed at 30‐min intervals from 10.00 to 15.00 h. Blood samples were collected every 10 min. The supraoptic nucleus (SON), paraventricular nucleus (PVN) and posterior pituitary were collected immediately after the experiment. Expression levels of mRNAs for oxytocin and peptidylglycine α‐amidating monooxygenase (PAM), the terminal enzyme in the oxytocin synthesis pathway, were measured using a real‐time polymerase chain reaction. Oxytocin peptide content in the posterior pituitary was measured by an enzyme‐linked immunosorbent assay, and plasma oxytocin concentration was measured by radioimmunoassay. Salsolinol treatment significantly up‐regulated oxytocin and PAM gene expression in the SON (P < 0.01 and P < 0.05, respectively), PVN (P < 0.01 and P < 0.05, respectively) and posterior pituitary (P < 0.05 and P < 0.05, respectively). Oxytocin peptide content in the posterior pituitary and the area under the response curve of plasma oxytocin were significantly (P < 0.05 and P < 0.01, respectively) higher in salsolinol‐treated sheep than in control animals. The present study shows for the first time that salsolinol stimulates oxytocin secretion during lactation in sheep.